An incentive for natural resource management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Apart from the issue of fairness, there is also considerable evidence that giving people secure rights to their land and natural resources, helps to ensure that land is properly maintained and resources are responsibly exploited. Ruth Meinzen-Dick, a researcher on land and water rights, explains the link.